Improved antibacterial activity of a sustained-release biocompatible nanofilm for treating Pseudomonas aeruginosa wound infection in vitro and in vivo - Feifei Lu; Guoxiu Lu; Zhiguo Wang; Wenzhua Wei; Jingjing Chen; Hailin Zheng; Xuesong Liu; Yan Ye; Shuling Liu; Yuxiang Lin; Yuxin Liu; Zhanhua Bi; et al. (Frontiers in Microbiology)
ObjectivesThe primary goal of this research was to design a useful and biocompatible nanofilm system (CNF) encapsulating chlorhexidine acetate (CHX) for wounds that is endowed with antibacterial and anti-inflammatory activities and promotes wound healing.MethodsThe nanofilm system was developed on the basis of the successful preparation of its nanoemulsion and PVA-CS film system and then important properties of the nanofilm system, including its morphological and physicochemical characteristics, stability and safety, its antimicrobial efficacy against P. aeruginosa was also evaluated in vitro and in vivo. The antibacterial effect, wound healing effect and inflammatory factor change in vivo were evaluated.ResultsThese results of this nanofilm system revealed a good particle size (59.27 nm) and stable zeta potential (−15.2 mV) that are suitable for wound healing applications. Additionally, it was stable, exhibited long-term stability (24 months) and sustained release in simulated wound fluid. Results showed that this nanofilm does not induce dose-related toxic effects and displays a better antibacterial effect that occurs more quickly, two times greater than that of CHX in vitro. This safe nanofilm enhances antibacterial activity against P. aeruginosa for 14 days, modulates the immune response, and accelerates skin wound healing in vivo.ConclusionsThese insights into multifunctional nanofilm designs for improved antibacterial effects and sustained release suggest promising clinical applications.